Restriction of nitric oxide rather than elevated blood pressure is responsible for alterations of vascular responses in nitric oxide-deficient hypertension - Holécyová, A; Török, J; Bernátová, I; Pechánová, O (Physiological research, 1996)
The responsiveness of isolated high-pressure (aorta, renal artery) and low-pressure vessels (pulmonary artery) was compared during systemic hypertension induced by chronic inhibition of nitric oxide synthesis by NG-nitro-L-arginine methyl ester (L-NAME) in rats. L-NAME (40 mg/kg/day) was given to animals in their drinking water. After 4 weeks of L-NAME treatment, systolic blood pressure increased by 37% as compared with that in the control group. Chronic L-NAME treatment resulted in significant reduction of endothelium-dependent relaxation to acetylcholine (10(-8) to 3 x 10(-6) mol/l) in both types of vessels. The reduced relaxation was not influenced by acute pretreatment with indomethacin (10(-5) mol/l), however, it was further reduced by acute pretreatment with additional L-NAME (10(-4) mol/l). L-arginine (10(-4) mol/l) improved the reduced relaxation. Endothelium-independent relaxation to sodium nitroprusside (10(-9) to 10(-6) mol/l) was unaffected by L-NAME treatment. beta-adrenoceptor-mediated relaxation to isoprenaline (10(-8) to 3 x 10(-6) mol/l) was also not influenced by chronic L-NAME treatment. Similar alterations in the responsiveness of high- and low-pressure vessels indicate rather the decisive role of nitric oxide restriction than that of elevated blood pressure in their development.
Keywords: Cyclooxygenase Inhibitors; aorta; vazodilatace; NG-Nitroarginine Methyl Ester; Vasodilation; Hypertension; plicní oběh; acetylcholin; oxid dusnatý; krysa rodu Rattus; inhibitory cyklooxygenasy; zvířata; Nitric Oxide; Pulmonary Circulation; Norepinephrine; vazokonstrikce; potkani Wistar; Adrenergic beta-Agonists; indomethacin; Isoproterenol; Acetylcholine; Rats, Wistar; Male; hypertenze; Indomethacin; agonisté adrenergních beta-receptorů; inhibitory enzymů; Rats; NG-nitroargininmethylester; noradrenalin; Animals; mužské pohlaví; Aorta; Vasoconstriction; isoprenalin; Enzyme Inhibitors; agonisté adrenergních alfa-receptorů; Adrenergic alpha-Agonists